THE ESSENCE OF FINANCIAL SECURITY AS AN OBJECT OF ANALYSIS (World of finance, 2023)
Introduction. In the conditions of the instability of the economic situation in Ukraine, the challenges and threats to the security of Ukraine are intensifying, in particular, there is an increase in the risks of inflation, the shadowing of the economy, and the legalization of illegal income. Therefore, it is important to rethink the theoretical prerequisites and the terminological and conceptual apparatus of the security sphere in the context of solving the current tasks of financial security analysis at all levels of the economic system of the state.The purpose of the article is to determine the content of economic and financial security as objects of analytical research based on the analysis of information from professional sources and current regulatory and legal acts.Results. It has been established that a stable state of the state's financial system is recognized as financially safe, under which the necessary financial conditions are created for its sustainable development and ensuring the stability of the country's financial system. For the purposes of financial security analysis, it is advisable to classify it at the following levels: global, state (national), regional, industry, business. The analysis of financial security at different levels allows to optimize information support for management decision-making, including taking into account strategic goals and the influence of the external environment.Conclusions. The essential content of the definitions "economic security", "financial security" has been developed and their content and functional characteristics have been revealed. A state is recognized as economically secure if its economic condition is stable, characterized by the balance of relevant indicators and invulnerability to external and internal threats, and ensures sustainable and effective development based on the observance of national economic interests. Financial security is a priority component of the economic security of the state. A stable state of the state's financial system is recognized as financially safe, under which the necessary financial conditions are created for its sustainable development and ensuring the stability of the country's financial system.Analysis of financial security at the global, state (national), regional, branch, and business levels allows for the formation of a scientifically based information field for making management decisions. The results of the analysis of the company's financial security allow timely diagnosis of the threat of bankruptcy and risks of economic activity. Analysis of financial security at the state level allows identifying real and potential threats to national interests in the financial sphere.